Community-Based Participatory Research and Fat Studies: Tensions and Alignments - Haney, Carly-Ann; Walsh, Christine A. (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2023)
Community-based participatory research (CBPR) is an overarching methodology taken up across various disciplines. Rather than a specific approach, CBPR encompasses varied action-based methodologies. While many disciplines use CBPR methodologies in their work, Fat Studies has yet to broadly create research that uses CBPR methodologies. Fat Studies counters many dominant fields that examine and pathologize the body. Rather than viewing Fat as a site of moral panic and concern, Fat Studies values the subjectivity, fluidity, and embodied experience of what it means to be Fat. As CBPR methodologies share a commitment towards critical, emancipatory, and social action research, the potential intersection with Fat Studies is noteworthy, however limited literature at this intersection exists. In this article, we highlight the alignments and tensions between CBPR and Fat Studies while offering future directions for scholars at this intersection.